Abdominal Compartment Syndrome in Patients with Abdominal Sepsis - Kryvoruchko, I. A.; Antonova, M. S.; Tonkoglas, O. A.; Goni, S.-K. T. (Journal of Education, Health and Sport, 2017)
Investigations were carried out in 53 patients who were operated on in 2015 about abdominal sepsis (AS). All patients were assigned according the severity of the condition, which was determined depending on the severity of the systemic inflammatory response and multiple organ failure: I group - patients with AS (28); II group - patients with severe AS (14); III group - patients with septic shock (11). Surgical management of all patients included two major components: control source of infection (source control) and control of organ damaged and the protective mechanisms system (damage control). In the first group, the laparotomy ended by suturing the wounds tightly with traditional drainage; in groups II and III surgical treatment were supplemented by the use of techniques aimed at the prevention and reduction of elevated intra-abdominal pressure. Studies have shown that 100 % of patients with AS showed an increase in intra-abdominal pressure and the development of intra-abdominal hypertension. While ACS developed in 18.9 % of cases (4 patients with severe sepsis and 6 - with septic shock). The highest mortality rate was observed among patients with grade III and IV intra-abdominal hypertension (11 of 25 patients).